2015
DOI: 10.1111/aphw.12051
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Self-Compassion and Well-Being: A Meta-Analysis

Abstract: The results clearly highlight the importance of self-compassion for individuals' well-being. Future research should further investigate the relationship between self-compassion and the different forms of well-being, and focus on the examination of possible additional moderators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

44
554
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 830 publications
(612 citation statements)
references
References 64 publications
44
554
0
14
Order By: Relevance
“…3 Self-compassion is also positively correlated with emotional intelligence, mindfulness, intrinsic motivation, and perceived self-competence. 4 Compassion towards others is associated with, for example, reduced levels of depression, 5 pro-social behaviour and social connectedness, 6 and reduced emotional supression.…”
Section: Preliminary Findingsmentioning
confidence: 98%
“…3 Self-compassion is also positively correlated with emotional intelligence, mindfulness, intrinsic motivation, and perceived self-competence. 4 Compassion towards others is associated with, for example, reduced levels of depression, 5 pro-social behaviour and social connectedness, 6 and reduced emotional supression.…”
Section: Preliminary Findingsmentioning
confidence: 98%
“…Neely et al (2009) defined well-being as low stress, negative affect and high life satisfaction. More specifically, psychological well-being, based on Zessin's, Dickhauser 's, & Garbade's (2015) insightful meta-analysis, seems to be a key factor for the eudemonia of people leading to a meaningful life and functioning and revealed a strong correlation of self-compassion and psychological well-being. Additionally, the same study indicated that subjective well-being entails cognitive well-being, which is characterized by the notion of life satisfaction and affective well-being, which is characterized by the notion of positive and negative effect.…”
Section: Self-compassion and Psychological Well-beingmentioning
confidence: 99%
“…A growing body of research suggests that self-compassion is positively associated with well-being (for an overview see Zessin, Dickhäuser, & Garbade, 2015) and negatively associated with depression (e.g. Costa & Pinto Gouveia, 2011; Gilbert, McEwan, Matos, & Rivis, 2011; Kuyken et al, 2010; Neff, Pisitsungkagarn, & Hseih, 2008; Raes, 2010, 2011; Roemer et al, 2009; van Dam, Sheppard, Forsyth, & Earleywine, 2011), anxiety (e.g.…”
mentioning
confidence: 99%